2008
DOI: 10.1007/s11195-008-9097-5
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Wishes and Need for Knowledge Concerning Sexuality and Relationships in Connection with Gynecological Cancer Disease

Abstract: The purpose of this study was to investigate women's wishes and need for knowledge concerning sexuality and relationships in connection with gynecological cancer. A total of 11 women were interviewed following the completion of their treatment for gynecological cancer. The data was analyzed using latent content analysis. Two main categories were identified: ''The absence of knowledge about the body'' and ''Conversation with sexual relevance.'' The women wished with their partners present, to be given more in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 6 publications
3
40
0
3
Order By: Relevance
“…In our study, surgical treatment was found to be applied most frequently; however, a diVerence was not found in mean scores of SQOL compared with other treatment types. In previous studies, the ratio of sexual dysfunction was found to range from 20 to 100% in gynaecological cancers [6,[21][22][23][24][25]. Anderson stated that many women resumed their daily lives but sexual problems were not resolved after cervical cancer treatment [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, surgical treatment was found to be applied most frequently; however, a diVerence was not found in mean scores of SQOL compared with other treatment types. In previous studies, the ratio of sexual dysfunction was found to range from 20 to 100% in gynaecological cancers [6,[21][22][23][24][25]. Anderson stated that many women resumed their daily lives but sexual problems were not resolved after cervical cancer treatment [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another important result obtained from this study, however, is that quality of life improves as the level of social support, especially spouse support, increases. In the literature, social support is reported to be important in improving quality of life in diseases aVecting life negatively like cancers [6,[21][22][23][24][25]. Spouse support in particular is reported to aVect treatment positively by signiWcantly reducing the psychological problems caused by the disease [26].…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the increasing body of research which consistently demonstrates that cancer can significantly impact sexual well-being (Bokhour, Clarke, Inui, Silliman, & Talcott, 2001;Mercadante, Vitrano, & Catania, 2012). For example, for women, cancer and associated treatments have been linked with long-term and permanent negative effects on sexual interest, vaginal lubrication (Jensen et al, 2004), menopausal status (Rasmusson & Thome´, 2008) and the experience of dyspareunia (Gilbert, Ussher, & Perz, 2010b, 2011. These effects have been found to induce 'invisible assaults to femininity' (Butler et al, 1998, p. 685), and are associated with diminished body image (Burns, Costello, Ryan-Woolley, & Davidson, 2007), a lack of sexual attractiveness and sexual confidence (Jensen et al, 2004), as well as dissatisfaction with intimate relationships (Weijmar Schultz, van de Wiel, & Bouma, 1991).…”
mentioning
confidence: 99%
“…This model allows health professionals to engage in the discussion of sexual changes at various levels of increasing intensity [23], starting with challenging the misconception that sexuality is ‘frivolous’ during cancer, by ‘giving permission’ for couples to talk about sex and be sexually intimate [24]. It potentially avoids providing information or interventions to people with cancer and partners that is not wanted or relevant [25], through encouraging the provision of ‘limited information’ in a written form, the preference of some patients [6]. If required, clinicians can provide ‘specific suggestions’ related to the adjustment to changes and expansion of sexual repertoires [26, 27], including sexual positioning or the use of sexual enhancement products [28, 29].…”
Section: Introductionmentioning
confidence: 99%